SOCIO-DEMOGRAPHIC STUDIES OF CANCER PATIENTS IN TERMS OF MEDICINAL PLANTS AS NEW RISK FACTOR AT CANCER HOSPITAL NIMRA, JAMSHORO - QURESHI , ST; JUNEJO , S; MALIK , S; MEMON , SA; SADIA, . (Biological and Clinical Sciences Research Journal, 2024)
Cancer is the third leading cause of mortality in Pakistan. Despite increased awareness about significant cancer risk factors and efforts to avoid them, cancer incidence continues to rise. This suggests that there may be other hidden physical and chemical agents responsible for cancer. Various plants used as long-term alternative medicine have recently been identified as genotoxic, capable of damaging DNA. Objective: This study aimed to identify medicinal plants with genotoxic potential and their association with cancer risk factors through a socio-demographic survey. Methods: This interview-based survey was conducted at the Nuclear Institute of Medicine & Radiotherapy (NIMRA) Cancer Hospital. The study included 109 cancer patients and was conducted over six months. Participants were categorized into four risk factor groups: other risk factors (ORF), other risk factors with medicinal plant (MP) intake (ORF+MPs), medicinal plants only (MPs), and only milk tea drinkers. Data were analyzed using descriptive statistics to determine the association between medicinal plant use and cancer incidence. Results: The survey revealed four risk factor categories: ORF, ORF+MPs, MPs, and tea. The highest number of cancer patients (49) were in the tea category, while the lowest (11) were in the MPs-only category. Among male cancer patients, 53% were ORF+MPs users, whereas 55% of female cancer patients were in the tea category. Most male and female MP users were older, less educated, unemployed or low-income, unmarried, and urban residents. Only 11 patients (8 female, three male) used 18 types of MPs for various health issues before their cancer diagnosis, with stomach gas being the most common problem. The duration of MP use ranged from 14 years to one month, and the interval between MP use and cancer diagnosis ranged from 10 to 1 year. Among female MP users, breast cancer was the most common, while each male MP user had different types of cancer (brain tumor, stomach cancer, and cheek cancer). The most frequently used MPs were beetroot (BR), pepper fruit (PF), and senna leaves (SL). Conclusion: Long-term intake of medicinal plants is more common in females and may constitute a new risk factor for cancer, particularly in individuals who do not interact with known risk factors. Genotoxicity tests on the identified medicinal plants are recommended.